Interactive Powerpoint Learning Media on Science Content for Fifth Grade Elementary School - Wirawan, I Made Tangkas Arya; Gading, I Ketut (Journal for Lesson and Learning Studies, 2022)
The absence of engaging learning resources impacts the effectiveness of student learning outcomes. This review aims to create a design and examine PowerPoint's viability, applicability, and efficacy for student learning outcomes in science subjects for fifth-grade Elementary School. Use the ADDIE Model for interactive learning ppt (Analyze, Design, Development, Implementation, Evaluation). The subjects of this research investigation were 11 grade 5 primary school children. Observation, interviews, rating scales, and tests are all employed as data collection techniques. The data analysis types employed are the evaluation process, instrument validity analysis, content validity analysis, practicality analysis, and effectiveness analysis. Two material specialists and two media experts conducted the feasibility test. Material experts earn a score of 0.93 (high validity), and media experts and media professionals receive a 0.89 score (high validity). For the practicality test, it got a score of 4.0 (very good). The effectiveness test using the correlated sample t-test test formula showed that the significant (2-tailed) was 0.000 (p<0.05). Learning media PowerPoint can effectively improve student learning outcomes, especially in the science content of Grade V Elementary School.